LANGUAGE STYLE USED BY THE MAIN CHARACTER ROMAN PEARCE IN “FAST & FURIOUS 9” MOVIE - Kelbulan, Beno; Mustikawati, Yunitari; Nurfadhilah, Auliyanti Sahril (ELITERATE : Journal of English Linguistics and Literature Studies, 2024)
Different sorts of dialect styles can be watched in little things in life and in numerous expressions. Each diverse environment will have a distinctive dialect fashion. This study discusses about fashion of dialect within the film script entitled Fast and Furious 9. In this study, the researcher points to study the style of dialect utilized by the most character "Roman Pearce". There’s two considers in this inquire about. To begin with, the researcher classifies all sorts of metaphorical dialect utilized by the most character "Roman Pearce" in "Fast and Furious 9” Motion picture. Moment, it clarifies all the components that impact the characters in utilizing distinctive dialect styles. This ponder employments sociolinguistics as an approach to examine the utilize of metaphorical dialect and to discover out the social variables that impact the utilize of complex dialect by characters in film scripts. The information is Fast and Furious 9 motion picture script. Information was collected by observing movies, perusing film scripts, and classifying dialect styles. The analyst chose the exchange talked by the most character. After collecting the information, the analyst separates and classifies these articulations into a few sorts of metaphorical dialect utilizing the hypothesis of Martin Joos (1976). At that point, the analyst found components that might impact the character to utilize dialect fashion by utilizing social figure hypothesis by Holmes and Wilson (2017). The discoveries appear that there are four sorts of metaphorical dialect utilized by Roman Pearce, the most character to Fast and Furious 9 movie. The four types of style are formal fashion, casual fashion, consultative fashion, and hint fashion. The foremost prevailing fashion of language utilized by the most character is the casual fashion (63%). The most character tends to utilize a relaxed style of dialect to make a more comfortable and loose environment. There are four social components that impact the two fundamental characters utilize metaphorical dialect, the four social variables are member, setting, point, and work.